Influence of magnetic field on morphological structures and physiological characteristics of bEnd.3 cells cultured on polypyrrole substrates. Issue 70 (11th December 2019) - Yang, Xue; Ma, Ke; Yang, Libo; Chen, Yujuan; Qu, Yingmin; Wang, Ying; Wang, Xinyue; Yang, Fan; Sun, Qi; Song, Zhengxun; Wang, Zuobin
Abstract : The combination of magnetic stimulation and polypyrrole (PPy) substrates regulate the bEnd.3 cells mechanical and physical characterizations. Abstract : This paper employs a spin-coated method to construct conductive polypyrrole (PPy) substrates which present superior properties for controlling the morphological structures and functions of bEnd.3 cells. The PPy substrates with a homogeneous particle size, uniform distribution and proper roughness show enhanced hydrophilic characteristics and improve cell adhesion to the substrates. The changes in the mechanical properties of cells and the responses to the designed substrates and magnetic field are also explored. Due to the synergistic effect between the magnetic field and the conductive PPy substrate, the cells cultured in such an environment exhibit applanate shapes with more branches and enhanced cell viability. In addition, the cells preferentially extend along the magnetic field direction. The mechanical characteristics of cells change significantly under varying magnetic intensity stimulations (5–16 mT). The satisfying effect on cells' morphology and outgrowth is acquired at the magnetic intensities of 9–10 mT and duration of 20 min, compared with other stimulated groups, while retaining cell viability. Moreover, the cells express higher adhesion up to 5.2 nN. The results suggest that the application of the PPy substrates and magnetic field is a promising candidate for the protection of neurovascular units and treatment of neurological diseases.